2020
DOI: 10.1101/2020.02.25.964528
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Gut microbiome, diet and symptom interactions in irritable bowel syndrome

Abstract: While several studies have documented associations between dietary habits and microbiota composition and function in healthy subjects, no study explored these associations in patients with irritable bowel syndrome (IBS), and especially in relation to symptoms. Here, we used a novel approach that combined data from 4-day food diary, integrated into a food tree, together with gut microbiota (shotgun metagenomic) for IBS patients (N=149) and healthy subjects (N=52). Paired microbiota and food-based trees allowed … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…Studies have confirmed that the body's homeostasis and the intestinal immune function depend on the balance of bacteria in different degrees, and once this balance is destroyed, it will lead to the occurrence of related diseases (Bruellman and Llorente, 2021;Han et al, 2021;Khan et al, 2021;Shute et al, 2021;Sun et al, 2021;Deng et al, 2022b;Hu et al, 2022). The dysregulation of gut microbiota can be caused by many factors, such as age (Du et al, 2021;Janiak et al, 2021), lifestyle (Pauer et al, 2021;Shin et al, 2021), dietary habits (Neumann et al, 2021;Tap et al, 2021;Yu et al, 2021), immunity (Foley et al, 2021;Hosseinkhani et al, 2021) and the use of antibiotics (Kang et al, 2021;Mcdonnell et al, 2021;Strati et al, 2021;Vicentini et al, 2021).…”
Section: Intestinal Microbiotamentioning
confidence: 99%
“…Studies have confirmed that the body's homeostasis and the intestinal immune function depend on the balance of bacteria in different degrees, and once this balance is destroyed, it will lead to the occurrence of related diseases (Bruellman and Llorente, 2021;Han et al, 2021;Khan et al, 2021;Shute et al, 2021;Sun et al, 2021;Deng et al, 2022b;Hu et al, 2022). The dysregulation of gut microbiota can be caused by many factors, such as age (Du et al, 2021;Janiak et al, 2021), lifestyle (Pauer et al, 2021;Shin et al, 2021), dietary habits (Neumann et al, 2021;Tap et al, 2021;Yu et al, 2021), immunity (Foley et al, 2021;Hosseinkhani et al, 2021) and the use of antibiotics (Kang et al, 2021;Mcdonnell et al, 2021;Strati et al, 2021;Vicentini et al, 2021).…”
Section: Intestinal Microbiotamentioning
confidence: 99%
“…Food and nutraceuticals are important for the gastrointestinal microbiome composition of humans and other animals (Lanng et al, 2021). Poor-quality food items consumed as main meals were reported to relate to severe irritable bowel syndrome in humans, as an enrichment of gut microbiota with a function toward a specific type of hydrogen metabolism associated with animal carbohydrate metabolism were detected in these cases (Tap et al, 2021). The dietary glucose oxidase could inhibit harmful bacteria and promote beneficial bacteria, which could be related to the improvement of the growth performance and intestinal barrier function in chickens (Zhao et al, 2021).…”
Section: Diet Improves Meat Quality By Altering Gut Microbiotamentioning
confidence: 99%
“…The dietary glucose oxidase could inhibit harmful bacteria and promote beneficial bacteria, which could be related to the improvement of the growth performance and intestinal barrier function in chickens (Zhao et al, 2021). Eubacterium rectale subspecies harboring flagellin-encoding genes were associated with a predominantly meat-based diet (Tap et al, 2021). Two of the three E. rectale subspecies were found to be associated with lower gut microbial community diversity, higher host BMI, and higher fasting blood insulin levels (Costea et al, 2017).…”
Section: Diet Improves Meat Quality By Altering Gut Microbiotamentioning
confidence: 99%